Prospective quality‐of‐life outcomes for low‐risk prostate cancer: Active surveillance versus radical prostatectomy. Issue 14 (6th April 2015) - Jeldres, Claudio; Cullen, Jennifer; Hurwitz, Lauren M.; Wolff, Erika M.; Levie, Katherine E.; Odem‐Davis, Katherine; Johnston, Richard B.; Pham, Khanh N.; Rosner, Inger L.; Brand, Timothy C.; L'Esperance, James O.; Sterbis, Joseph R.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND For patients with low‐risk prostate cancer (PCa), active surveillance (AS) may produce oncologic outcomes comparable to those achieved with radical prostatectomy (RP). Health‐related quality‐of‐life (HRQoL) outcomes are important to consider, yet few studies have examined HRQoL among patients with PCa who were managed with AS. In this study, the authors compared longitudinal HRQoL in a prospective, racially diverse, and contemporary cohort of patients who underwent RP or AS for low‐risk PCa. METHODS Beginning in 2007, HRQoL data from validated questionnaires (the Expanded Prostate Cancer Index Composite and the 36‐item RAND Medical Outcomes Study short‐form survey) were collected by the Center for Prostate Disease Research in a multicenter national database. Patients aged ≤75 years who were diagnosed with low‐risk PCa and elected RP or AS for initial disease management were followed for 3 years. Mean scores were estimated using generalized estimating equations adjusting for baseline HRQoL, demographic characteristics, and clinical patient characteristics. RESULTS Of the patients with low‐risk PCa, 228 underwent RP, and 77 underwent AS. Multivariable analysis revealed that patients in the RP group had significantly worse sexual function, sexual bother, and urinary function at all time points compared with patients in the AS group. Differences in mental health between groups were below the threshold for clinical significance at 1 year. CONCLUSIONS In this study, no differences in mental health outcomes were observed, but urinary and sexual HRQoL were worse for patients who underwent RP compared with those who underwent AS for up to 3 years. These data offer support for the management of low‐risk PCa with AS as a means for postponing the morbidity associated with RP without concomitant declines in mental health. Cancer 2015;121:2465–2473. © 2015 American Cancer Society.